Characterization of the effect of ion irradiation on industrially produced GdBa2Cu3O7−δ superconducting tapes using a slow positron beam. (3rd December 2020) - Yabuuchi, Atsushi; Ozaki, Toshinori; Sakane, Hitoshi; Okazaki, Hiroyuki; Koshikawa, Hiroshi; Yamamoto, Shunya; Yamaki, Tetsuya
Abstract: To investigate the effect of irradiation-induced defects on the superconducting characteristics of industrially produced superconductor—GdBa2 Cu3 O7− δ (GdBCO)—coated conductors (CCs), we irradiated the GdBCO CCs with Au ions at 2 or 10 MeV and probed them using a slow positron beam. Vacancy clusters were detected in both unirradiated and irradiated GdBCO CCs. However, the effect of ion irradiation on the GdBCO CCs was characterized as a slight reduction in the positron annihilation rate with low-momentum electrons. We also found a correlation between the annihilation rate of low-momentum electrons and the superconducting transition temperature.